Changes of acetylcholinesterase activity in different rat brain areas following intoxication with nerve agents: biochemical and histochemical study - Bajgar, Jiri; Hajek, Petr; Slizova, Dasa; Krs, Otakar; Fusek, Josef; Kuca, Kamil; Jun, Daniel; Bartosova, Lucie; Blaha, Vaclav (Chemico-biological interactions, 2007)
Acetylcholinesterase activity in defined brain regions was determined using biochemical and histochemical methods 30 min after treating rats with sarin, soman or VX (0.5 x LD(50)). Enzyme inhibition was high in the pontomedullar area and frontal cortex, but was low in the basal ganglia. Histochemical and biochemical results correlated well. Determination of the activity in defined brain structures was a more sensitive parameter than determination in whole brain homogenate where the activity was a "mean" of the activities in different structures. The pontomedullar area controls respiration, so that the special sensitivity of acetylcholinesterase to inhibition by nerve agents in this area is important for understanding the mechanism of death caused by nerve agents. Thus, acetylcholinesterase activity is the main parameter investigated in studies searching for target sites following nerve agent poisoning.
Keywords: acetylcholinesterasa; Basal Ganglia; Cholinesterase Inhibitors; Rats; apoptóza; soman; potkani Wistar; Animals; Apoptosis; Frontal Lobe; zvířata; sarin; chemické bojové látky; krysa rodu Rattus; čelní lalok; Rats, Wistar; ženské pohlaví; cholinesterasové inhibitory; Female; Acetylcholinesterase; bazální ganglia; Soman; Sarin; Chemical Warfare Agents